GARP inhibits allergic airway inflammation in a humanized mouse model. Issue 9 (1st April 2016) - Meyer‐Martin, H.; Hahn, S. A.; Beckert, H.; Belz, C.; Heinz, A.; Jonuleit, H.; Becker, C.; Taube, C.; Korn, S.; Buhl, R.; Reuter, S.; Tuettenberg, A.
Abstract: Background: Regulatory T cells (Treg) represent a promising target for novel treatment strategies in patients with inflammatory/allergic diseases. A soluble derivate of the Treg surface molecule glycoprotein A repetitions predominant (sGARP) has strong anti‐inflammatory and regulatory effects on human cells in vitro as well as in vivo through de novo induction of peripheral Treg. The aim of this study was to investigate the immunomodulatory function of sGARP and its possible role as a new therapeutic option in allergic diseases using a humanized mouse model. Methods: To analyze the therapeutic effects of sGARP, adult NOD/ Scid γc −/− (NSG) mice received peripheral blood mononuclear cells (PBMC) derived from allergic patients with sensitization against birch allergen. Subsequently, allergic inflammation was induced in the presence of Treg alone or in combination with sGARP. Results: In comparison with mice that received Treg alone, additional treatment with sGARP reduced airway hyperresponsiveness (AHR), influx of neutrophils and macrophages into the bronchoalveolar lavage (BAL), and human CD45 + cells in the lungs. Furthermore, the numbers of mucus‐producing goblet cells and inflammatory cell infiltrates were reduced. To elucidate whether the mechanism of action of sGARP involves the TGF‐β receptor pathway, mice additionally received anti‐TGF‐β receptor II (TGF‐βRII) antibodies. Blocking the signaling of TGF‐β through TGF‐βRII abrogated the anti‐inflammatory effects of sGARP, confirming its essential role in inhibiting the allergic inflammation. Conclusion: Induction of peripheral tolerance via sGARP is a promising potential approach to treat allergic airway diseases.